2021
DOI: 10.5217/ir.2020.00017
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors for venous thrombosis among patients with inflammatory bowel disease in China: a multicenter retrospective study

Abstract: of other veins such as intra-abdominal venous thrombosis. Patients with IBD, including Crohn' s disease (CD) and ulcerative colitis (UC), have an average of 2-to 4-fold risk for venous thrombosis compared to the healthy population. 1-4 Venous thrombosis results in an increased mortality rate, especially in patients who developed PE. 5,6 The development of venous thrombosis among IBD patients is a multifactorial process that follow the triad of Virchow. 7 Active inflammation further increased such risk, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
(99 reference statements)
0
5
0
Order By: Relevance
“…We identified an additional 13 during the screening of the reference sections of the included studies. Eighteen studies met inclusion criteria; 17 of the included studies were retrospective cohort studies ( 22 , 24 32 , 34 , 35 , 42 47 ), one of the included studies was a case-control study ( 48 ) ( Figure 1 ). The data was extracted in a tabular format and has been summarized in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…We identified an additional 13 during the screening of the reference sections of the included studies. Eighteen studies met inclusion criteria; 17 of the included studies were retrospective cohort studies ( 22 , 24 32 , 34 , 35 , 42 47 ), one of the included studies was a case-control study ( 48 ) ( Figure 1 ). The data was extracted in a tabular format and has been summarized in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“… 40 , 42 - 44 Several risk factors are more common in IBD patients than in the general population, including hyperhomocysteinemia, dehydration, infection, prolonged immobilization, and active intestinal disease. 40 , 42 , 45 In addition, the risk of VTE in IBD patients may increase when it is accompanied by other diseases known to be risk factors for VTE. This hypothesis is supported by the fact that the HR value for VTE gradually increased with CCI score in this study.…”
Section: Discussionmentioning
confidence: 99%
“…One study 87 has shown that the incidence of venous thrombosis in IBD patients in China is 41.45/100 000. Numerous studies [88][89][90][91] have reported that the risk of thrombosis increases at the active stage of severe UC.…”
Section: Thromboprophylaxis and Treatmentmentioning
confidence: 99%